Barriers to attachment? Relationships among constraints, attachment, and visitation to urban parks. (September 2019) - Rushing, Jaclyn R.; Needham, Mark D.; D'Antonio, Ashley; Metcalf, Elizabeth Covelli
Abstract: This article examined constraints to visiting urban parks, whether constraints varied between traditionally well-served (white majority) and underserved (minorities) populations, and relationships among constraints, visitation, and place attachment for these groups. Data from two samples of Portland, Oregon (US) residents ( n  = 620, 2708) showed the primary constraints were limited knowledge about these parks, lack of access, and being too busy. There were minimal differences in these and most other constraints between underserved and well-served groups, but underserved residents were more constrained by race and cultural issues (e.g., lack of park visitor and staff diversity). There were no differences between groups in visitation or attachment associated with their favorite park. Constraints and visitation explained 20% of the variance in attachment for well-served residents and 29–32% for underserved residents, and constraints explained 3–18% of the variance in visitation for well-served residents and 9–11% for underserved residents. The strongest negative predictor of attachment for both groups was these parks not being the best places, and strong positive predictors for both groups were visitation frequency and lack of park facilities and services. For well-served residents, race and cultural issues were also strong predictors of attachment. For underserved residents, limited knowledge about these parks was also a strong predictor. The only predictors of visitation were fear, access, and costs. Management implications: Managers of these parks might reduce constraints and increase visitation and attachment by improving awareness through advertising, increasing diversity (e.g., staff, visitors, programs), partnering with community organizations, enhancing facilities and services, making these parks safer and more accessible and affordable, and investigating what would make their parks interesting, welcoming, well-known, and better choices. Management Implications: No differences between well-served and underserved residents in visitation suggests these agencies may be meeting their objective of reaching a diversity of residents, but constraints from limited knowledge, access, and being too busy suggests managers might consider improving advertising, access, and public transportation to parks. Underserved residents were more constrained by racial and cultural issues, and lack of park facilities. Managers might consider increasing staff diversity, creating programs for minorities, partnering with community organizations, and enhancing facilities. Some constraints were important for attachment, especially for underserved residents. These constraints included access, disinterest, knowledge, these parks not being the best, and racial and cultural issues. Managers might consider investigating what would make their parks interesting, welcoming, well-known, and better choices. Visitation was a strong predictor of attachment, and visitation was related to fear, access, and costs. Managers might consider making parks safe, accessible, and affordable (e.g., discounted pricing, lighting, staff presence).